Targeted and untargeted metabolomics uncovering the effects of Jiawei Ermiao Granule on patients with persistent HPV infection - Xiu Li; Xiu Li; Li Ning; Li Ning; Hongting Zhao; Yating Xu; Yating Xu; Yu Si; Yu Si; Jiayi Hua; Qingling Ren; Qingling Ren (Frontiers in Cellular and Infection Microbiology)
Jiawei Ermiao Granule (JWEMG) is a traditional Chinese herbal formulation widely used in China for the treatment of human papilloma virus (HPV) infections. However, the mechanisms underlying their efficacy in clearing HPV infections remain unclear. This study aimed to elucidate the mechanisms by which JWEMG clears persistent HPV infections from a metabolomics perspective using modern analytical techniques. Untargeted and targeted metabolomics analyses were performed on vaginal lavage samples from 33 patients using liquid chromatograph mass spectrometer (LC-MS) and hydrophilic interaction liquid chromatography-mass spectrometry (HILIC-MS). Untargeted metabolomics identified 47 potential biomarkers through volcano plot analysis, among which 30 exhibited a reversal trend following JWEMG intervention. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis suggested that JWEMG may exert therapeutic effects on patients with persistent HPV infections via pathways related to starch and sucrose metabolism, galactose metabolism, fructose and mannose metabolism, and amino sugar and nucleotide sugar metabolism. Targeted metabolomics revealed a significant increase in tyrosine levels in the vaginal/cervical microenvironment following JWEMG treatment. By integrating targeted and untargeted metabolomics, this study provides a comprehensive exploration of the holistic effects of JWEMG on HPV-infected patients, addressing the challenges of scientifically explaining the pharmacological mechanisms of multi-component, multi-target traditional Chinese medicines.